Bruger- og ekspertinddragelse ved udarbejdelse af online (fag)ordbøger: det kooperative princip i leksikografien - Leroyer, Patrick (Nordiske Studier i Leksikografi, 2018)
This article outlines the tenets of a cooperative framework between expert-users, experts and lexicographers in the construction of not only specialised, online dictionaries but also of language for general purposes dictionaries. Firstly, the article briefly explains why the topic of cooperation with experts has not attracted the attention it deserves: this is due to the side effects of what might be called general language lexicographic hegemony, in which a strong consensual focus is awarded to general language dictionaries and to knowledge of language. Secondly, the article briefly refers to a few case studies of lexicographic cooperation – and of its counterpart, absence of cooperation. Finally, a cooperation model is presented on the basis of two closely related cooperation theses. It is concluded that lexicography could benefit from a greater interest in specialised lexicography in order to adequately meet the knowledge needs of dictionary users in the modern knowledge and information society.